The Influence of Bank-Specific Variables and Macroeconomics on Rural Banks with High-Level Non-Performing Loans - Cuandra, Fendy; Wijaya, Alexander Janio (Politeknik Negeri Bengkalis, 2023)
Rural banks’ roles as financing services have become a great contributor to Indonesia’s MSME business. This study aims to examine the firm performance of rural banks in the Province of West Nusa Tenggara, Indonesia. The bank-specific variable and macroeconomics are used to test the effect on the rural banks with a high NPL level in Indonesia’s province. This study employs the panel data regression with semi-annual reports of 17 rural banks from 2017-2021. The effect of NPL, CAR, bank size, LDR, GDP growth rate, inflation rate, interest rate, and exchange rate on ROA and ROE were analyzed. NPL was found positively affect ROA but doesn’t affect ROE. While both CAR and bank size positively affect ROA but don’t affect ROE. Moreover, the LDR doesn’t affect both ROA and ROE.